Social Sciences Learning Model - Syafruddin, Syafruddin; Irmalasari, Irmalasari; haznah, Nur; adwiah, Radiatul; Yuniar, Vira (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is to evaluate various social studies learning models implemented in elementary schools, see the effectiveness of each model, and identify the challenges faced in their implementation. Qualitative research methods were used by conducting classroom observations, interviews with teachers, and analysis of documents related to the curriculum and learning materials. The research results show that various social studies learning models, such as cooperative learning, project-based learning, problem-based learning, and skills-based learning, have their respective advantages and disadvantages in the context of learning in elementary schools. However, in general, it was found that project-based learning and problem-based learning had a more positive impact on students' understanding of social studies concepts and the development of social skills.